Overview of Student Understanding in Research Statistics Lectures Using the PJBL Method - Islawati Islawati; Munawwarah Munawwarah (Jurnal Studi Guru dan Pembelajaran, 2024)
The main issue in this study is that many students still have difficulty integrating theory with practice, particularly at the stages of data visualization and interpretation. This study aims to explore students' understanding of data collection and analysis techniques in research statistics courses through the implementation of the Project-Based Learning (PJBL) method. A qualitative descriptive approach was used in this study, involving 22 students from the Chemistry Education Program. Students were applied to each stage of PJBL, namely: (1) Determining the Main Question, (2) Compiling a Project Plan, (3) Collecting and Analyzing Data, (4) Compiling Results and Interpretation, and (5) Project Evaluation. The results showed that students demonstrated a good understanding at the initial stages, such as Determining the Main Question and Compiling a Project Plan, which reflects their ability to understand and design the data analysis process. At more complex stages, such as Data Collection and Analysis and Compiling Results and Interpretation, it was found that some students had difficulty connecting the analysis results with the research context. Students' reflections during the Project Evaluation phase indicated that they were aware of the challenges they faced, such as the in-depth understanding of data visualization and interpretation techniques, as well as the importance of applying theory to practice. This study highlights the importance of the PJBL approach in supporting experiential learning to enhance students' understanding of research statistical techniques. Through in-depth exploration, this study provides insights into the learning challenges and the potential of project-based learning strategies to enhance students' research skills in higher education.